2018
DOI: 10.1021/acs.joc.8b02397
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonative Metalation of Methoxy-Substituted Arenes Using Lithium 2,2,6,6-Tetramethylpiperidide: Experimental and Computational Study

Abstract: The reaction pathways of lithium 2,2,6,6-tetramethylpiperidide (LiTMP)-mediated deprotonative metalation of methoxy-substituted arenes were investigated. Importantly, it was experimentally observed that, whereas TMEDA has no effect on the course of the reactions, the presence of more than the stoichiometric amount of LiCl is deleterious, in particular without an in situ trap. These effects were corroborated by the DFT calculations. The reaction mechanisms, such as the structure of the active species in the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
11
0
1
Order By: Relevance
“…Previous results from the group showed that 1-phenylindole could be efficiently deprotonated at C2 by using a base prepared from ZnCl 2 ∙TMEDA (TMEDA = N , N , N ′, N ′-tetramethylethylenediamine) and LiTMP (TMP = 2,2,6,6-tetramethylpiperidino) in a 1:3 ratio [ 47 , 48 , 49 ]. Indeed, after treatment of the substrate by this formed 1:1 LiTMP-Zn(TMP) 2 mixture of amides [ 47 , 50 , 51 ] in THF at room temperature (rt) and addition of iodine to intercept the heteroarylmetal obtained, 2-iodo-1-phenylindole was isolated with a yield of 92% [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous results from the group showed that 1-phenylindole could be efficiently deprotonated at C2 by using a base prepared from ZnCl 2 ∙TMEDA (TMEDA = N , N , N ′, N ′-tetramethylethylenediamine) and LiTMP (TMP = 2,2,6,6-tetramethylpiperidino) in a 1:3 ratio [ 47 , 48 , 49 ]. Indeed, after treatment of the substrate by this formed 1:1 LiTMP-Zn(TMP) 2 mixture of amides [ 47 , 50 , 51 ] in THF at room temperature (rt) and addition of iodine to intercept the heteroarylmetal obtained, 2-iodo-1-phenylindole was isolated with a yield of 92% [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent computer study on anisole showed that the reactive species is solvated LiTMP. The effectiveness of the reaction derives from the stabilizing effect of the transmetalation step [21]. …”
Section: Resultsmentioning
confidence: 99%
“…The use of in situ metal traps avoids the use of cryogenic conditions to achieve these reactions [16,17]. We have developed mixed lithium-zinc combinations based on TMP (TMP = 2,2,6,6-tetramethylpiperidino) capable of deprotonating sensitive substrates at temperatures close to rt [18,19,20,21]. In order to obtain original scaffolds such as pyrazino-fused carbazoles and carbolines, we decided to combine this deprotometalation under in situ trapping conditions with palladium- and copper-catalyzed coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Because the 1:1 LiTMP-Zn(TMP)2 (TMP = 2,2,6,6-tetramethylpiperidino) mixture of amides, formed by mixing LiTMP and ZnCl2•TMEDA in a 3:1 ratio, [55][56][57] is a powerful base for obtaining aromatic deprotometalation, 44 we then decided to explore the use of chiral versions to attempt enantioselective reactions. To do this, we replaced the TMP groups of 1:1 LiTMP-Zn(TMP)2 with chiral amino groups coming from H-exo-born-R and H-endo-born-S (Scheme 2).…”
Section: Study Using Lithium-zinc Amides Prepared From Chiral Exo-(αr...mentioning
confidence: 99%